Anti-blooming effect of graphene oxide on natural rubber latex composite films. (12th April 2019) - Huang, Shasha; Hou, Jiarui; Yin, Jin; Zhang, Zejun; Ding, Beibei; Duan, Yongxin; Zhang, Jianming
Abstract: Owing to its water-dispersibility and compatibility with natural rubber latex (NRL) in an aqueous medium, graphene oxide (GO), the precursor of graphene, has been often employed as an emerging filler for improving the mechanical and barrier properties of NRL products. Herein, to solve the blooming problem of NRL products, we studied the anti-blooming effect of GO in NRL-GO composites. The NRL-GO composite films were prepared by latex compounding followed by solution casting. Scanning electron microscopy and energy dispersive X-ray spectrometry were employed to characterize the NRL/GO microstructure and analyze the anti-blooming effect. The results reveal significant enhancement of the anti-blooming performance of the composite films with GO, even at a GO content as low as 0.5 wt%. The origin of the anti-blooming effect of GO is discussed in terms of three factors: 1) inner-layered structure of GO in the composite films, 2) interaction between GO and the additives, and 3) surface property of the composite films. This work not only provides a new strategy to overcome the severe blooming issue of NRL products, but also expands the practical application of GO in traditional NRL industry.